Communication from the Virginia Paymaster General charging Colonels Snyder and Bailey with defrauding the state : February 19, 1862 (Document (Virginia. General Assembly. Senate), 1862)
1862 Communication from the the Virginia Paymaster General, with accompanying ten documents, relating to a gross fraud on the Treasury, committed by Colonel John Snyder commanding the 135th regiment of Virginia militia and Colonel A.C. Bailey commanding the 142nd regiment Virginia militia. This communication was submitted to the General Assembly, along with various recommendations from Governor Letcher.